Effectiveness of digital advertising in Kathmandu Valley - Mishra, Akalesh Kumar; Sah, Kishan; Bhatta, Sushmita (Nepalese Journal of Management, 2024)
This study examines the effectiveness of digital advertising in Kathmandu Valley. Consumer purchase decision is selected as the dependent variable. Similarly, digital advertising, email marketing, social media marketing, mobile marketing and blog are selected as independent variables. The primary source of data is used to assess the opinions of the respondents regarding effectiveness of digital marketing on consumer buying behavior in Kathmandu Valley. This study is based on primary data with 122 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of digital advertising on consumer purchase decision in Kathmandu Valley. The study showed that digital advertising has a positive impact on consumer purchase decisions. It means that better digital advertising leads to increase in consumer purchase decisions. Similarly, email marketing has a positive impact on consumer purchase decisions. It indicates that increase in email marketing leads to increase in consumer purchase decisions. Moreover, social media marketing has a positive impact on consumer purchase decisions. It means that increase in social media marketing leads to increase in consumer purchase decisions. Likewise, mobile marketing has a positive impact on consumer purchase decisions. It shows that the increase in mobile marketing leads to increase in consumer purchase decisions. Further, blog has a positive impact on consumer purchase decisions. It shows that uniqueness in blog leads to increment in consumer purchase decisions.